PEMANFAATAN SAMPAH ORGANIK RUMAH TANGGA DALAM PEMBUATAN PUPUK BOKASHI BAGI MASYARAKAT DESA EMPAT NEGERI KEC. DATUK LIMA PULUH KAB. BATU BARA - Yenni Asbur; Yayuk Purwaningrum; Murni Sari Rahayu; Rahmi Dwi Handayani Rambe; Dedi Kusbiantoro; Khairunnisyah Khairunnisyah; Surya Dharma (Universitas Islam Sumatear Utara, 2021)
Empat Negeri is one of the villages in the Datuk Lima Puluh Batu Bara. Along with the expansion of an area, there will be an increase in population and organic and inorganic waste. One form of organic waste management is the manufacture of Bokashi which can reduce the waste problem while creating economic value from the waste. The purpose of this Community Service is to increase the awareness of the people of the village of Empat Negeri, Datuk Lima Puluh, Batu Bara towards the use of household organic waste into Bokashi fertilizer which is beneficial for agriculture and a sustainable environment. The method of this activity is in the form of training for the community of Empat Negeri village, Datuk Lima Puluh, Batu Bara to utilize household organic waste into bokashi fertilizer. The results of the evaluation during this activity can be seen that the awareness of the community in the village of Empat Negeri, District of Datuk Lima Puluh, to sort and process household waste has increased. People are starting to realize that good household waste management is beneficial for the environment, and can provide added value economically.